Persons with Disability (PWDs) in Rural Philippines: Results from the 2010 Field Survey in Rosario, Batangas - Aubrey D. Tabuga; Christian D. Mina; Celia M. Reyes; Ronina D. Asis; Maria Blesila G. Datu (Philippine Institute for Development Studies (PIDS), 2011)
In an effort to complement the 2008 disability survey conducted in Metro Manila, the University of Tokyo and the Philippine Institute for Development Studies collaborated to undertake a similar study in a rural area. The survey was conducted in Rosario, Batangas in 2010, where 106 PWDs from 31 barangays were interviewed.Some of the major findings of the survey are as follows: The majority of the respondents did not even finish elementary education. The most common reason for not going to school ever or completing schooling is poverty. Employment rate among the respondents, however, is slightly lower (at 47%) than that in Metro Manila (50%). If the visually-impaired has the highest proportion with income-generating jobs (72%) in Metro Manila (who are usually masseurs), the hearing-impaired has the highest employment rate (58%) in Rosario, who are usually farmers/farm workers. Very few of the respondents are members of the Municipal Federation of PWDs, which is the only Disability Self-Help Organization in Rosario. Moreover, only 3 out of 10 respondents are aware of the important policies that were intended to improve their well-being. Among the 31 respondents who have knowledge about any of the policies on discounts, only 10 of them have ever enjoyed at least one of these discounts and possess a PWD ID card. Lack of awareness and participation stem from not having the chance to go out and mingle with other people reflecting the social, economic, and physical constraints that PWDs in rural areas are facing.
Keywords: 330; Philippines; macroeconomic outlook; persons with disability (PWDs); rural; survey; Rosario; Batangas; livelihood; Behinderte; Soziale Lage; Bildungsniveau; Erwerbstätigkeit; Ländlicher Raum; Philippinen